Correction to: Segregation of a novel p.(Ser270Tyr) MAF mutation and p.(Tyr56*) CRYGD variant in a family with dominantly inherited congenital cataracts - Dudakova, Lubica; Stranecky, Viktor; Ulmanova, Olga; Hlavova, Eva; Trková, Marie; Vincent, Andrea L; Liskova, Petra (Molecular biology reports, 2017)
There was a spacing error in the initial online publication, and there were errors in the Acknowledgments section. The original article has been updated.